Nonlinear hybrid control design of three-joint dual finger robots. (1st February 2017) - Chen, Yung-Yue; Chang, Tzu-Ching; Chen, Yung Hsiang; Chen, Qi-Xian
The difficulty of finger robot grasping control designs is the inevitable coupling in the dynamics of finger joints and finger tips because this dynamics coupling effect lets the overall motion of the finger robots to be constrained by the object states when they are controlled to manipulate an object's postures. Besides, from the practical implementation point of view, a stable and easy-to-implement control structure is also an important task for this topic. For solving these two design issues, an optimal hybrid control design which combines feedback linearization and nonlinear H 2 control concepts for grasping design of three-joint dual finger robots is investigated in this study. This investigation makes two main contributions to the finger robot grasping control design: (1) an effective and acceptable control performance for finger robot grasping control designs under the effect of dynamics coupling is delivered and (2) a really simple nonlinear optimal control scheme is obtained.